The Implementation of Student Administration at SMK Muhammadiyah 1 Palembang - Sari, Dona Fitri; Arwan; Maryance (The Future of Education Journal, 2026)
Student administration is an essential component of educational management that supports the effective, efficient, and sustainable implementation of the educational process. It encompasses not only student data recording but also student services, guidance, and the development of learners’ potential from admission through graduation. This study aims to provide an in-depth analysis of the implementation of student administration and to identify the supporting and inhibiting factors affecting its implementation at SMK Muhammadiyah 1 Palembang. This research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving key informants, including administrative staff and the vice principal for student affairs, as well as the principal as a supporting informant. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of student administration at SMK Muhammadiyah 1 Palembang has been relatively effective, integrating both manual and digital systems, particularly in the areas of new student admissions and student data management. The main supporting factors include leadership commitment, interdepartmental coordination, effective communication, and the availability of facilities and infrastructure. However, several challenges remain, such as students’ low discipline in completing administrative requirements and the suboptimal integration of data due to the use of multiple non-centralized systems.